Pengaruh current ratio, return on assets, dan receivable turnover terhadap harga saham - Adityaputra, Stephanus Andi Adityaputra (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2023)
This study aims to examine and identify the effect of the Current Ratio, Return on Assets, and Receivable Turnover on Stock Prices. The research sample was determined using a purposive sampling technique so that a total of 71 samples were obtained from technology sector companies listed on the Indonesia Stock Exchange for three years, namely from 2020 to 2022. The data analysis method was carried out using Multiple Linear Regression using IBM SPSS Statistics software version 25. The results of this study indicate that the Current Ratio, Return on Assets, and Receivable Turnover simultaneously affect stock prices. Return on Assets and Receivable Turnover have a positive effect on stock prices. On the other hand, the Current Ratio has no effect on the Stock Price.